INTERVAL OSCILLATION CRITERIA FOR HIGHER ORDER NEUTRAL NONLINEAR DIFFERENTIAL EQUATIONS WITH DEVIATING ARGUMENTS - Xu, Run; Meng, Fanwei (Journal of the Indonesian Mathematical Society, 2009)
"Pdf File"DOI :Â http://dx.doi.org/10.22342/jims.15.1.41.21-35